Low-negative-pressure sodium battery and preparation method thereof

By using prelithiated hard carbon particles negative electrodes, core-shell structure positive electrodes and specific electrolytes in sodium ion batteries, the problems of sodium ion batteries in high temperature, high magnification and long-term cycle stability are solved, and higher battery performance and service life are achieved.

CN119864495AActive Publication Date: 2025-04-22FUJIAN SHIJI HUANA NEW ENERGY TECHNOLOGY GROUP CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202510083117.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-22
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

Existing sodium ion batteries have insufficient performance in terms of high temperature, high rate discharge and long-term cycle stability, especially poor rate performance of negative electrode materials, insufficient high temperature stability of positive electrode materials, and stability of electrolytes.

Method used

Prelithiated hard carbon particles are used as the negative electrode material, the positive electrode material of the core-shell structure, specific electrolyte formulations and porous separators to improve the cycle stability and high-temperature performance of the battery through these technical means.

Benefits of technology

It significantly improves the cycle stability and high temperature performance of the battery, extends the service life of the battery, and enhances the safety and performance stability of the battery in extreme operating conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864495A_ABST
    Figure CN119864495A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical energy storage, and discloses a low-negative-pressure sodium battery which comprises a negative electrode material, a positive electrode material, electrolyte and a diaphragm, the negative electrode material is hard carbon particles subjected to pre-lithiation treatment, the particle size is 5-10 m, and the surface of the negative electrode material is coated with a polyvinylidene fluoride-hexafluoropropylene functional layer; the invention also discloses a preparation method of the low-negative-pressure sodium battery, which comprises the following steps: S1, preparing a negative electrode material: mixing the hard carbon particles and the lithium metal sheet according to a mass ratio of 1: (0.4-0.6), and carrying out heat treatment at 400-450 DEG C for 2-3 hours. The hard carbon negative electrode material subjected to pre-lithiation treatment is adopted, so that the stability of the battery under high-rate and long-cycle conditions is remarkably improved; through the design of the positive electrode material with the core-shell structure, the structural stability and the capacity retention ratio of the battery in a high-temperature environment are enhanced; and by optimizing the electrolyte formula, the ionic conductivity and the decomposition resistance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical energy storage, and in particular to a low negative pressure sodium battery and a preparation method thereof. Background Art

[0002] Sodium-ion batteries have become one of the hot topics of research in recent years due to their advantages such as low cost and abundant resources. Especially in large-scale energy storage and low-cost application scenarios, they have shown greater potential than lithium-ion batteries. However, although sodium-ion batteries have great application prospects in theory, some technical bottlenecks in existing technologies still restrict their performance and application expansion, especially in terms of high temperature, high rate discharge and long-term cycle stability.

[0003] First of all, the selection of negative electrode materials for sodium-ion batteries has always been one of the bottlenecks restricting their performance improvement. At present, hard carbon is considered to be the most promising negative electrode material because of its high specific capacity, good electrical conductivity and good cycle performance. However, a major problem in the practical application of hard carbon materials is that they are prone to large capacity decay during high-rate discharge. This is because the structure of hard carbon is relatively loose, and the embedding and de-embedding process of sodium ions inside it can easily lead to structural collapse, which in turn affects the cycle life and capacity retention of the battery. In addition, the pore structure and surface properties of hard carbon are also key factors affecting its electrochemical performance. Many existing technologies use simple surface coatings or additives to improve the performance of hard carbon, but these methods fail to fundamentally solve the problems of poor rate performance and stability under high loads.

[0004] Secondly, the positive electrode material of sodium-ion batteries is also a focus of research. Layered oxide materials, as a major choice for positive electrode materials, have received widespread attention due to their high theoretical capacity and good conductivity. However, layered oxide materials are prone to phase change during long-term use, causing their capacity to gradually decline, affecting the overall performance of the battery. Especially under high temperature conditions, this phase change phenomenon is more obvious, resulting in an unstable material structure, which in turn significantly reduces the energy density and safety of the battery. In order to address this problem, some researchers have tried to improve the high-temperature stability of layered oxide materials by doping elements or constructing composite materials, but these methods often fail to effectively solve the phase change problem of the material, and some materials have high costs and complex preparation processes, making them difficult to apply on a large scale.

[0005] The stability of the electrolyte is also one of the key factors affecting the performance of sodium-ion batteries. Most sodium-ion batteries use sodium hexafluorophosphate (NaPF6) as the sodium salt and a carbonate solvent system. Although sodium hexafluorophosphate has good electrochemical stability, the performance of its electrolyte often decreases significantly under high voltage and high temperature environments. Especially under high temperature conditions, the decomposition of the electrolyte and the deposition of sodium salts may lead to increased internal resistance of the battery, electrolyte failure, and even short circuit, which seriously affects the safety and life of the battery. Moreover, in the existing sodium-ion battery electrolyte system, the types and amounts of additives used have not yet achieved the optimal stability and power characteristics, and the high-rate performance and long cycle life of the battery are still limited.

[0006] In addition, existing sodium-ion batteries have poor stability at high temperatures, which is particularly prominent in many applications. Under high temperature conditions, irreversible reactions may occur between battery materials and electrolytes, leading to increased internal pressure in the battery, capacity decay, and even safety accidents. Because temperature changes accelerate the degradation of the electrolyte and structural damage to the electrode materials, traditional sodium-ion batteries often cannot operate at high temperatures for a long time, which limits their use in high-temperature applications.

[0007] In summary, although the existing sodium-ion battery technology has shown significant potential in some areas, it still has major technical defects due to issues such as the rate performance of negative electrode materials, the high-temperature stability of positive electrode materials, and the stability of electrolytes. How to optimize the battery material system and improve the stability of the battery under high temperature and high rate conditions is still an important challenge in current sodium-ion battery research. Summary of the invention

[0008] In view of the deficiencies of the prior art, the present invention provides a low negative pressure sodium battery and a preparation method thereof, which solves the problems of battery capacity decay, poor rate performance and instability at high temperatures in the prior art.

[0009] To achieve the above objectives, the present invention is implemented by the following technical solutions: A low negative pressure sodium battery, comprising a negative electrode material, a positive electrode material, an electrolyte and a diaphragm, wherein: The negative electrode material is pre-lithiation treated hard carbon particles with a particle size of 5-10 μm and a polyvinylidene fluoride-hexafluoropropylene functional layer coated on the surface; The cathode material is a core-shell structure, including: The core layer is made of layered oxide material NaNi x Mn 1-x O2 composition, where x is 0.7-0.8; The shell is composed of sodium phosphate, and the mass of the shell accounts for 5-15% of the total mass of the positive electrode; The electrolyte includes sodium hexafluorophosphate, ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, a sodium salt concentration of 0.8-1.2M, and additives include fluoroethylene carbonate in an addition ratio of 2-5% and N-methyl-N-propylpyrrolidinium bisfluorosulfonimide in an addition ratio of 15-25%; The diaphragm is a porous diaphragm with a porosity of 40-50% and a thickness of 16-25 μm.

[0010] Preferably, the porosity of the hard carbon particles of the negative electrode material is 25-40%.

[0011] Preferably, the core layer grain size of the positive electrode material is 1-5 μm.

[0012] A method for preparing a low negative pressure sodium battery comprises the following steps: S1. Preparation of negative electrode material: Mix hard carbon particles and lithium metal sheets in a mass ratio of 1:0.4-0.6, heat treat at 400-450°C for 2-3h, and after cooling, coat the surface with 3-6% polyvinylidene fluoride-hexafluoropropylene solution, and heat treat at 70-100°C after drying; S2. Preparation of positive electrode material: Sodium carbonate, nickel oxide and manganese oxide are weighed in a molar ratio of 1:0.7-0.8:0.2-0.3, ball-milled for 10-12 hours, pre-sintered at 500-550°C for 5-7 hours, and then sintered at 850-900°C for 10-12 hours to form a core layer; The core material is coated with a sodium phosphate solution, dried, and then sintered at 500-550°C for 3-5h to form a shell layer; S3, electrolyte preparation: 0.8-1.2M sodium hexafluorophosphate is dissolved in a mixed solvent of EC:DMC with a volume ratio of 1:1, 2-5% fluoroethylene carbonate and 15-25% N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide are added, and stirred evenly; S4, battery assembly: stack the positive electrode, separator and negative electrode in sequence, inject the electrolyte and seal, and perform 3-5 pre-cycles at a rate of 0.05C. Preferably, the heat treatment atmosphere in the preparation of the negative electrode material in step S1 is high-purity argon, and the argon flow rate is 50-100 ml / min.

[0013] Preferably, the positive electrode material in step S2 is prepared by immersion coating.

[0014] Preferably, in the step S3, the stirring speed in the preparation of the electrolyte is 300-600 rpm, the stirring time is 2-4 hours, and the water content in the solution is controlled below 10 ppm.

[0015] The present invention provides a low negative pressure sodium battery and a preparation method thereof. The battery has the following beneficial effects: 1. The present invention adopts a technical solution of pre-lithiation treatment of hard carbon particles, so that the negative electrode material has higher conductivity and better sodium ion embedding ability, which significantly improves the cycle stability of the battery. Compared with the solution of directly using traditional hard carbon materials in the prior art, the pre-lithiation treatment can reduce the adsorption of lithium ions on the surface of hard carbon particles, avoid the problems of capacity decay and battery performance degradation during the cycle process, and significantly improve the service life and stability of low negative pressure sodium batteries.

[0016] 2. The present invention optimizes the conduction and stability of sodium ions in the positive electrode material by introducing a core-shell structure into the positive electrode material. The core layer adopts a layered oxide material and the shell layer is a sodium phosphate coating. Compared with the simple synthesis method of traditional positive electrode materials, the present invention can effectively avoid the problems of electrolyte decomposition and thermal runaway when the battery is overcharged. This design significantly improves the safety of the battery under extreme working conditions and improves the performance degradation of the battery after long-term use.

[0017] 3. The present invention adopts a specific electrolyte formula, which combines sodium hexafluorophosphate with a mixed solvent of ethylene carbonate and dimethyl carbonate, and adds fluoroethylene carbonate and N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide. This innovative formula significantly improves the performance of the battery in low temperature environments, especially in terms of charge and discharge rate and cycle stability. Compared with traditional electrolyte formulas, the new electrolyte can maintain higher ion conductivity at low temperatures, greatly improving the working efficiency of the battery in cold environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Please see attached Figure 1 , an embodiment of the present invention provides a low negative pressure sodium battery, comprising a negative electrode material, a positive electrode material, an electrolyte and a separator, wherein: The negative electrode material is pre-lithiation treated hard carbon particles with a particle size of 5-10 μm and a polyvinylidene fluoride-hexafluoropropylene functional layer coated on the surface; The cathode material is a core-shell structure, including: The core layer is made of layered oxide material NaNi x Mn 1-xO2 composition, where x is 0.7-0.8; The shell is composed of sodium phosphate, and the mass of the shell accounts for 5-15% of the total mass of the positive electrode; The electrolyte includes sodium hexafluorophosphate, ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, a sodium salt concentration of 0.8-1.2M, and additives include fluoroethylene carbonate in an addition ratio of 2-5% and N-methyl-N-propylpyrrolidinium bisfluorosulfonimide in an addition ratio of 15-25%; The diaphragm is a porous diaphragm with a porosity of 40-50% and a thickness of 16-25 μm.

[0021] The hard carbon particles of the negative electrode material have a porosity of 25-40%.

[0022] The core layer grain size of the positive electrode material is 1-5μm.

[0023] A method for preparing a low negative pressure sodium battery, characterized in that it comprises the following steps: S1. Preparation of negative electrode material: Mix hard carbon particles and lithium metal sheets in a mass ratio of 1:0.4-0.6, heat treat at 400-450°C for 2-3h, and after cooling, coat the surface with 3-6% polyvinylidene fluoride-hexafluoropropylene solution, and heat treat at 70-100°C after drying; S2. Preparation of positive electrode material: Sodium carbonate, nickel oxide and manganese oxide are weighed in a molar ratio of 1:0.7-0.8:0.2-0.3, ball-milled for 10-12 hours, pre-sintered at 500-550°C for 5-7 hours, and then sintered at 850-900°C for 10-12 hours to form a core layer; The core material is coated with a sodium phosphate solution, dried, and then sintered at 500-550°C for 3-5h to form a shell layer; S3, electrolyte preparation: 0.8-1.2M sodium hexafluorophosphate is dissolved in a mixed solvent of EC:DMC with a volume ratio of 1:1, 2-5% fluoroethylene carbonate and 15-25% N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide are added, and stirred evenly; S4. Battery assembly: stack the positive electrode, separator and negative electrode in sequence, inject the electrolyte and seal, and perform 3-5 pre-cycles at a rate of 0.05C.

[0024] The heat treatment atmosphere in the preparation of the negative electrode material in step S1 is high-purity argon gas, and the argon gas flow rate is 50-100 ml / min.

[0025] In step S2, the positive electrode material is prepared by an immersion coating method.

[0026] In step S3, the stirring speed in the electrolyte preparation is 300-600 rpm, the stirring time is 2-4 hours, and the water content in the solution is controlled below 10 ppm.

[0027] Example 1: Preparation of high-efficiency low-negative-pressure sodium battery Step 1: Preparation of negative electrode materials Hard carbon particles and lithium metal sheets were uniformly mixed in a mass ratio of 1:0.5. The mixture was placed in a high-purity argon atmosphere with a flow rate of 80 mL / min and heat treated at 400°C for 2 hours. After the heat treatment, it was cooled to room temperature. Then, a 3.5% polyvinylidene fluoride-hexafluoropropylene solution was coated on the surface, dried at 70°C after uniform coating, and finally heat treated at 100°C for 1 hour.

[0028] Step 2: Preparation of positive electrode materials Weigh sodium carbonate, nickel oxide and manganese oxide, mix them in a molar ratio of 1:0.75:0.25, and ball mill for 12 hours. Pre-sinter the ball-milled powder at 500°C for 6 hours, and then sinter at 850°C for 11 hours to obtain the core layer. The surface of the core material is coated with sodium phosphate solution, and then sintered at 500°C for 4 hours to form a shell layer. The positive electrode material finally obtains a layered structure, the core layer grain size is about 3μm, and the shell layer mass accounts for 8% of the total mass.

[0029] Step 3: Preparation of electrolyte Dissolve 1M sodium hexafluorophosphate in a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) at a volume ratio of 1:1 and stir evenly. Then, add 3% fluoroethylene carbonate and 20% N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide and stir for 4 hours to ensure that the solution is completely uniform. During the stirring process, keep the water content in the solution below 10ppm.

[0030] Step 4: Battery Assembly The negative electrode, positive electrode and porous diaphragm are stacked in sequence, the porosity of the diaphragm is maintained at 45%, and the thickness is about 20μm. The prepared electrolyte is added, and the battery is sealed and pre-cycled at a rate of 0.05C for 3 times. After the pre-cycle, the battery has good charge and discharge performance and performs well in low temperature environment.

[0031] Example 2: Low negative pressure sodium battery with optimized negative electrode material and electrolyte formulation Step 1: Preparation of negative electrode materials The hard carbon particles and lithium metal sheets were mixed at a mass ratio of 1:0.45, and after being mixed evenly, they were heated to 420°C in an argon atmosphere and kept for 2.5 hours. After cooling to room temperature, 4% polyvinylidene fluoride-hexafluoropropylene solution was applied, and after the coating was evenly applied, it was placed in an oven and dried at 80°C for 3 hours, and then heat treated at 90°C for 1 hour.

[0032] Step 2: Preparation of positive electrode materials Sodium carbonate, nickel oxide and manganese oxide were weighed and mixed in a molar ratio of 1:0.8:0.2. After ball milling for 10 hours, they were pre-calcined at 510°C for 6 hours and then sintered at 870°C for 11 hours to form a core layer. The core material was immersed in a sodium phosphate solution, coated and sintered at 530°C for 4 hours to form a shell layer. The grain size of the layered structure of this positive electrode material was controlled within 2μm, and the mass of the shell layer accounted for 10% of the total mass of the positive electrode.

[0033] Step 3: Preparation of electrolyte Dissolve 0.9M sodium hexafluorophosphate in an equal volume of a mixed solvent of ethylene carbonate and dimethyl carbonate, add 4% fluoroethylene carbonate and 18% N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide, and stir until uniform for 3 hours. The water content in the solution is kept below 15ppm.

[0034] Step 4: Battery Assembly The negative electrode, separator, and positive electrode are stacked in order, with the separator porosity maintained at 42% and the thickness at 18μm. After injecting the above electrolyte, the battery is sealed and pre-cycled 4 times, each time at a charge and discharge rate of 0.05C to ensure the capacity stability of the battery.

[0035] Example 3: Low negative pressure sodium battery on a fully automated production line Step 1: Preparation of negative electrode materials The hard carbon particles were mixed with lithium metal sheets at a mass ratio of 1:0.55, and heated at 430°C for 2.5 hours using a high-purity argon atmosphere with an argon flow rate of 70 mL / min. After cooling to room temperature, a 5% polyvinylidene fluoride-hexafluoropropylene solution was used for coating and dried at 80°C for 3 hours. Finally, heat treatment was performed at 95°C for 1 hour to ensure the stability of the negative electrode material.

[0036] Step 2: Preparation of positive electrode materials Sodium carbonate, nickel oxide and manganese oxide were weighed and mixed in a molar ratio of 1:0.7:0.3. After ball milling for 12 hours, they were pre-calcined at 520°C for 7 hours and sintered at 880°C for 12 hours to form a core layer. Sodium phosphate solution was coated on the surface of the core material, dried and sintered at 530°C for 5 hours to form a shell layer. The final positive electrode material layered structure had a grain size of 4μm, and the shell layer mass accounted for 6% of the total mass.

[0037] Step 3: Preparation of electrolyte 1.0M sodium hexafluorophosphate was dissolved in an equal volume of a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC), and 3% fluoroethylene carbonate and 22% N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide were added, and stirred evenly for 4 hours. Finally, the water content in the solution was controlled below 12ppm.

[0038] Step 4: Battery Assembly The negative electrode, separator and positive electrode are stacked in sequence using an automated production line, with the separator porosity controlled at 50% and the thickness at 20 μm. After the electrolyte is injected, the battery is immediately sealed and pre-cycled at a rate of 0.05C for 5 times.

[0039] Example 4: Preparation of high performance sodium battery under low temperature conditions Step 1: Preparation of negative electrode materials The hard carbon particles and lithium metal sheets were mixed in a mass ratio of 1:0.5 and placed in an argon atmosphere for heat treatment at 440°C for 2 hours. After cooling, the surface was coated with a 4% polyvinylidene fluoride-hexafluoropropylene solution, dried, and then heat treated at 90°C for 1 hour.

[0040] Step 2: Preparation of positive electrode materials Sodium carbonate, nickel oxide and manganese oxide were mixed in a molar ratio of 1:0.7:0.3, ball milled for 10 hours, pre-calcined at 500°C for 7 hours, and sintered at 850°C for 12 hours to form a core layer. Sodium phosphate solution was coated on the surface of the core material, dried, and sintered at 520°C for 5 hours to form a shell layer.

[0041] Step 3: Preparation of electrolyte 0.8M sodium hexafluorophosphate was dissolved in an equal volume of a mixed solvent of ethylene carbonate and dimethyl carbonate, 3% of fluoroethylene carbonate and 15% of N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide were added, and stirred evenly to ensure that the water content in the solution was less than 10 ppm.

[0042] Step 4: Battery Assembly The positive electrode, separator and negative electrode are stacked in sequence, the separator porosity is controlled at 45% and the thickness is 18μm. After the electrolyte is injected, it is sealed and pre-circulated for 5 times with a rate of 0.05C.

[0043] Comparative Example 1: The negative electrode material was not pre-lithiated Comparative Example 1 Preparation steps: Preparation of negative electrode materials: Hard carbon particles and lithium metal sheets were mixed in a mass ratio of 1:1, heat treated at 400°C for 2h, and after cooling, the surface was not coated with any functional layer and directly proceeded to the next step.

[0044] Preparation of positive electrode materials: Sodium carbonate, nickel oxide and manganese oxide were weighed in a molar ratio of 1:0.75:0.25, ball-milled for 12 hours, pre-calcined at 500°C for 6 hours, and then sintered at 850°C for 11 hours to form a core layer; the core material was coated with sodium phosphate solution, dried, and sintered at 550°C for 4 hours to form a shell layer.

[0045] Preparation of electrolyte: 1M sodium hexafluorophosphate was dissolved in a mixed solvent of ethylene carbonate and dimethyl carbonate (volume ratio 1:1), 5% fluoroethylene carbonate and 20% N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide were added, and stirred for 2 h. The water content in the solution was controlled below 20 ppm.

[0046] Battery assembly: The positive electrode, separator (porosity 40%, thickness 20 μm) and negative electrode are stacked in sequence, and the electrolyte is injected and sealed. The battery is pre-cycled for 5 times at a rate of 0.1C.

[0047] Comparative Example 2: Adjustment of the ratio of the core layer of the positive electrode material Comparative Example 2 Preparation steps: Preparation of negative electrode material: According to step S1 in Example 1, pre-lithiated hard carbon particles are used to coat the polyvinylidene fluoride-hexafluoropropylene functional layer.

[0048] Preparation of positive electrode materials: Sodium carbonate, nickel oxide and manganese oxide were weighed in a molar ratio of 1:0.5:0.5, ball-milled for 12 hours, pre-calcined at 500°C for 5 hours, and then sintered at 850°C for 10 hours to form a core layer; the core material was coated with sodium phosphate solution, dried, and sintered at 550°C for 5 hours to form a shell layer.

[0049] Preparation of electrolyte: 1M sodium hexafluorophosphate was dissolved in a mixed solvent of ethylene carbonate and dimethyl carbonate (volume ratio 1:1), 3% fluoroethylene carbonate and 18% N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide were added, and stirred for 3 h. The water content in the solution was controlled below 15 ppm.

[0050] Battery assembly: The positive electrode, separator (porosity 45%, thickness 22μm) and negative electrode are stacked in sequence, and sealed after injecting electrolyte. The battery is pre-cycled for 5 times at a rate of 0.05C.

[0051] Comparative Example 3: Change of the ratio of additives in the electrolyte Comparative Example 3 Preparation steps: Negative electrode material preparation: Hard carbon particles without pre-lithiation were used and coated with a polyvinylidene fluoride-hexafluoropropylene functional layer. The particle size of the hard carbon particles was 8 μm and the porosity was 35%.

[0052] Preparation of positive electrode materials: Sodium carbonate, nickel oxide and manganese oxide were weighed in a molar ratio of 1:0.7:0.3, ball-milled for 10 hours, pre-calcined at 500°C for 6 hours, and then sintered at 850°C for 11 hours to form a core layer; the core material was coated with sodium phosphate solution, dried, and sintered at 530°C for 3 hours to form a shell layer.

[0053] Preparation of electrolyte: 1.0 M sodium hexafluorophosphate was dissolved in a mixed solvent of ethylene carbonate and dimethyl carbonate (volume ratio 1:1), 1% fluoroethylene carbonate and 10% N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide were added, and stirred for 2 h. The water content in the solution was controlled below 25 ppm.

[0054] Battery assembly: The positive electrode, separator (porosity 42%, thickness 18μm) and negative electrode are stacked in sequence, and the electrolyte is injected and sealed. The battery is pre-cycled 3 times at a rate of 0.1C.

[0055] Comparative Example 4: Adjustment of the number of pre-cycles during battery assembly Comparative Example 4 Preparation steps: Preparation of negative electrode material: Use hard carbon particles that have been pre-lithiated, and coat the surface with a polyvinylidene fluoride-hexafluoropropylene functional layer. The particle size of the hard carbon particles is 7 μm and the porosity is 30%.

[0056] Preparation of positive electrode materials: Sodium carbonate, nickel oxide and manganese oxide were weighed in a molar ratio of 1:0.7:0.2, ball-milled for 11 hours, pre-calcined at 510°C for 6 hours, and then sintered at 860°C for 11 hours to form a core layer; the core material was coated with sodium phosphate solution, dried, and sintered at 540°C for 4 hours to form a shell layer.

[0057] Preparation of electrolyte: 0.9 M sodium hexafluorophosphate was dissolved in a mixed solvent of EC and DMC (volume ratio 1:1), 4% fluoroethylene carbonate and 17% N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide were added, and stirred for 2 h. The water content in the solution was controlled below 10 ppm.

[0058] Battery assembly: The positive electrode, separator (porosity 43%, thickness 19μm) and negative electrode are stacked in sequence, and the electrolyte is injected and sealed. The battery is pre-cycled for 7 times at a rate of 0.1C.

[0059] Experiment 1: Charging and discharging performance test under low temperature environment Experimental steps: Battery preparation: According to Example 1 and Comparative Example 1, two groups of sodium batteries were prepared respectively. The experimental group (Example 1) used a pre-lithiated hard carbon particle negative electrode, a core-shell structure positive electrode, and a specific electrolyte and a porous separator; while Comparative Example 1 did not perform pre-lithiation treatment in the negative electrode material, and used traditional sodium cobalt oxide as the positive electrode material.

[0060] When assembling the battery, the positive electrode, separator, and negative electrode are stacked in order to ensure the sealing of the battery assembly. Then the electrolyte is injected and the battery is packaged.

[0061] Environmental conditions setting: The batteries were placed at -20°C, 0°C and 25°C ambient temperatures for charge and discharge tests.

[0062] All cells were pre-cycled 5 times at -20 °C to ensure cell stability.

[0063] Charge and discharge cycle: At different temperatures, use constant current charging / discharging equipment to perform charge and discharge tests. The current for each charge and discharge is 0.2C of the battery capacity (i.e., the battery charge and discharge rate is 20% of its rated capacity). Each charge is to 3.2V and the discharge is to 2.0V. Record the charge and discharge curves and the capacity change of the battery.

[0064] Under different ambient temperatures, the battery voltage, discharge capacity and battery internal resistance during charging were recorded.

[0065] Data Collection and Analysis: The charge and discharge curve records of each battery group include charging time, maximum voltage, current intensity and charging efficiency.

[0066] After the test is completed, the internal resistance and discharge capacity of each battery are measured. The final data will be used to compare the performance differences between the example and comparative example batteries under different temperature conditions.

[0067] Experimental data: Table 1: Charge and discharge performance data under low temperature environment Summary: The experimental data clearly reflect the excellent performance of the battery of Example 1 in a low temperature environment, especially at -20°C, the discharge capacity and internal resistance of Example 1 are better than those of the battery of Comparative Example 1. It can be inferred that the pre-lithiation-treated hard carbon particles improve the performance of the battery in a low temperature environment by introducing an additional lithium source into the negative electrode material. This pre-lithiation treatment not only increases the porosity of the negative electrode, but also effectively improves the conductivity of the negative electrode, thereby providing more stable charge and discharge performance at low temperatures.

[0068] In addition, the combination of the layered oxide positive electrode material and the sodium phosphate shell in Example 1 helps to improve the structural stability of the positive electrode, especially when the viscosity of the electrolyte increases at low temperatures, the stability of the positive electrode material and the internal resistance of the battery as a whole are reduced, further optimizing the cycle performance of the battery. This is consistent with the mechanism in the design of the present invention, making full use of the advantages of the pre-lithiation negative electrode material, and solving the problem of rapid battery capacity decay at low temperatures by optimizing the positive electrode material.

[0069] In contrast, since no pre-lithiation treatment was performed in Comparative Example 1, the conductivity of the negative electrode was low, and the structural stability of the positive electrode material was poor, resulting in increased internal resistance and more obvious capacity decay in a low temperature environment. In general, the design of Example 1 can not only effectively improve the charge and discharge performance at low temperatures, but also extend the service life of the battery, providing a more efficient and reliable battery solution for applications such as new energy storage and electric vehicles.

[0070] Experiment 2: Cyclic stability and capacity retention test Experimental steps: Battery preparation: According to Example 2 and Comparative Example 2, two groups of sodium batteries were prepared respectively. Example 2 used a pre-lithiated hard carbon particle negative electrode, the positive electrode used a core-shell structure, the electrolyte was a mixed solution of sodium hexafluorophosphate and dimethyl carbonate (DMC), and fluoroethylene carbonate and N-methyl-N-propylpyrrolidinium bisfluorosulfonimide were added. Comparative Example 2 used a conventional sodium negative electrode material (without pre-lithiation) and a sodium cobalt oxide positive electrode, and the electrolyte was a conventional sodium hexafluorophosphate and dimethyl carbonate (DMC) solution.

[0071] Ambient temperature setting: All batteries were tested at 25℃ for 300 cycles. During the test, the discharge capacity and internal resistance of the battery were tested after every 50 charge and discharge cycles. Each charge was to 3.2V and the discharge was to 2.0V.

[0072] Charge and discharge cycle process: The battery is charged and discharged at a rate of 0.5C, and the discharge capacity and internal resistance of each cycle are recorded. After every 50 cycles, the battery voltage, capacity, internal resistance and other data are tested and recorded.

[0073] At the end of each charge and discharge, the battery internal resistance test was carried out and the electrochemical impedance spectrum of the battery was measured using the AC impedance method (AC impedance).

[0074] Data Collection and Analysis: Statistics and analysis of the initial capacity of each battery group and the capacity decay during the cycle process.

[0075] The data for each cycle is recorded and ultimately compared based on the overall cycling stability of the batteries.

[0076] Experimental data: Table 2: Cyclic stability and capacity retention test data Summary: From the experimental results, the capacity retention of Example 2 after 300 charge and discharge cycles is significantly better than that of Comparative Example 2. After 300 cycles, the battery of Example 2 can still maintain a high capacity, and the increase in internal resistance is small. This is closely related to the technical solution of the present invention, especially in the pre-lithiation treatment of the negative electrode material. The pre-lithiation process improves the stability and conductivity of the hard carbon particles, so that the battery shows better stability after long-term cycling.

[0077] At the same time, the core-shell structure design of the positive electrode material also helps the battery maintain its capacity during long-cycle charge and discharge. The combination of the core layer of the layered oxide and the sodium phosphate shell reduces the structural damage and capacity attenuation caused by high-rate charge and discharge. Therefore, the battery's cycle performance has been effectively improved, and it can maintain a low internal resistance during long-term use.

[0078] In contrast, in the battery of Comparative Example 2, the negative electrode material has not been pre-lithiated, resulting in poor conductivity during the cycle, and the structural stability of the positive electrode material is insufficient. As the use cycle increases, the internal resistance of the battery increases and the capacity decays significantly. This further verifies the important role of pre-lithiated hard carbon particles and core-shell structure positive electrodes in improving battery cycle performance. This technical solution not only improves the cycle life of the battery, but also reduces the energy loss of the battery, providing a more reliable solution for practical applications.

[0079] Experiment 3: Rate performance test Experimental steps: Battery preparation: According to Example 3 and Comparative Example 3, two groups of sodium batteries were prepared respectively. Example 3 used a pre-lithiated hard carbon particle negative electrode, the positive electrode was a core-shell structure, the electrolyte was a mixed solution of sodium hexafluorophosphate and ethylene carbonate, and fluoroethylene carbonate and N-methyl-N-propylpyrrolidinium bisfluorosulfonimide were added. Comparative Example 3 used a conventional hard carbon negative electrode, the positive electrode was sodium cobalt oxide, and the electrolyte was a solution of sodium hexafluorophosphate and dimethyl carbonate (DMC).

[0080] Rate test conditions: The battery was placed in a constant temperature environment for testing at 25°C. Different rates were set for charge and discharge testing: 0.1C, 0.5C, 1C, 2C, 5C. The charge voltage at each rate was 3.2V, and the discharge cut-off voltage was 2.0V. Each charge and discharge cycle was maintained for at least two times, and the discharge capacity at each rate was recorded.

[0081] Test steps: Each battery was pre-charged and discharged twice at a rate of 0.1C to stabilize battery performance. After that, the charge and discharge tests were carried out at rates of 0.5C, 1C, 2C, and 5C. After each charge and discharge test, the discharge capacity, internal resistance, and voltage data of the battery were recorded.

[0082] After each test, the AC impedance method is used to detect the internal resistance of the battery and analyze the electrochemical performance of the battery.

[0083] Data Collection: Record and analyze the discharge capacity, internal resistance change and charge voltage / discharge voltage characteristics of the battery at each rate. Test the relationship between capacity attenuation and internal resistance increase at each rate.

[0084] Experimental data: Table 3: Rate performance test data Summary: In the rate performance test, the battery of Example 3 showed significant superiority, especially under high rate charge and discharge conditions, it can still maintain a relatively high discharge capacity, and the increase in the internal resistance of the battery is small. This is because the pre-lithiation hard carbon particle negative electrode effectively enhances the conductivity of the battery at high rates, allowing the battery to be efficiently charged and discharged in a short period of time without prone to capacity decay. At the same time, the stability of the core-shell structured positive electrode material at high rates is also improved, and the sodium phosphate shell effectively prevents the structural disintegration of the material, thereby reducing the increase in the internal resistance of the battery.

[0085] The battery of Comparative Example 3 performs poorly at high rates, especially at rates above 1C, where the discharge capacity decreases significantly and the internal resistance increases significantly. This phenomenon can be attributed to the fact that the hard carbon particle negative electrode, which has not been pre-lithiated, has a large charge transfer impedance during high-rate charge and discharge, resulting in a decrease in battery performance. At the same time, the stability of the sodium cobalt oxide positive electrode material is insufficient, especially during high-rate charge and discharge, the electrode material is prone to irreversible changes, resulting in a decrease in the conductivity inside the battery, thereby showing poor rate performance.

[0086] In general, the battery of Example 3 is superior to that of Comparative Example 3 in rate performance, indicating that the combination of the pre-lithiation hard carbon anode and the core-shell structure cathode of the present invention can not be ignored in improving the high rate performance. These structural optimizations effectively improve the conductivity and stability of the battery, and are particularly suitable for application scenarios requiring high rate charge and discharge.

[0087] Experiment 4: Cyclic stability test Experimental steps: Battery preparation: According to Example 4 and Comparative Example 4, two groups of sodium batteries were prepared respectively. Example 4 used pre-lithiated hard carbon particles as the negative electrode, the positive electrode adopted a core-shell structure, and the electrolyte was a mixed solution of sodium hexafluorophosphate, ethylene carbonate, fluoroethylene carbonate and N-methyl-N-propylpyrrolidinium bisfluorosulfonimide. Comparative Example 4 used conventional hard carbon negative electrode materials, the positive electrode was sodium cobalt oxide, and the electrolyte was a mixed solution of sodium hexafluorophosphate and dimethyl carbonate.

[0088] Cycle test conditions: The battery was first pre-cycled twice (0.1C rate, charge cut-off voltage of 3.2V, discharge cut-off voltage of 2.0V). Then, it was set to charge and discharge at 1C rate, and the discharge capacity was recorded after each cycle. The test cycle was 300 times.

[0089] Test steps: After each battery is initially charged and discharged at a rate of 0.1C, it is adjusted to a rate of 1C for cycle testing. The capacity of each discharge and the voltage change during charge and discharge are recorded. After each test, the internal resistance change of the battery is recorded, and the internal resistance of the battery is tested using the electrochemical impedance spectroscopy (EIS) method to analyze the performance degradation of the battery during multiple cycles.

[0090] Data Collection: The capacity retention rate, internal resistance increase and voltage change of the battery after 300 cycles were recorded and compared to evaluate the battery's cycle stability and long-term performance.

[0091] Experimental data: Table 4: Cyclic stability test data Summary: After 300 cycles, the sodium battery of Example 4 maintained a relatively high discharge capacity with a small increase in internal resistance. This shows that the pre-lithiation-treated hard carbon particle negative electrode and the core-shell structured positive electrode material used in the present invention can effectively inhibit the capacity decay and internal resistance increase of the battery in long-term cycles. This phenomenon may be related to the pre-lithiation treatment of the hard carbon particles. The pre-lithiation process increases the stability and conductivity of the negative electrode and reduces the structural changes of the electrode material during the cycle. In addition, the core-shell structure of the positive electrode effectively protects the layered oxide material and prevents its disintegration during multiple charges and discharges, thereby extending the service life of the battery.

[0092] The battery of Comparative Example 4 has obvious capacity decay and rapid internal resistance growth under the same cycle test. As the number of cycles increases, the battery capacity gradually decreases while the internal resistance increases significantly, which indicates that the performance degradation of conventional hard carbon negative electrodes and sodium cobalt oxide positive electrodes is more serious under high-rate charge and discharge and long-term cycles. In particular, the sodium cobalt oxide positive electrode is prone to structural disintegration, resulting in increased internal resistance and capacity decay.

[0093] By comparison, the battery of Example 4 exhibits excellent cycle stability, which indicates that the long-term performance of the battery can be significantly improved through reasonable electrode material design and optimization of electrolyte formulation. The capacity retention rate and internal resistance change trend of the battery demonstrate the advantages of the present invention in cycle performance, and it is particularly suitable for energy storage devices that require long life and stable performance.

[0094] Experiment 5: High temperature stability test Experimental steps: Battery preparation: Two groups of sodium batteries were prepared according to Example 5 and Comparative Example 5. Example 5 used pre-lithiation treated hard carbon particles as the negative electrode, and the positive electrode was a core-shell structure. The electrolyte was a mixed solution of sodium hexafluorophosphate, ethylene carbonate, fluoroethylene carbonate and N-methyl-N-propylpyrrolidinium bisfluorosulfonimide. Comparative Example 5 used a conventional hard carbon negative electrode and a sodium cobalt oxide positive electrode, and the electrolyte was a mixed solution of sodium hexafluorophosphate and dimethyl carbonate.

[0095] High temperature environment test conditions: The two groups of batteries were placed in temperature environments of 45°C, 55°C, and 65°C for charge and discharge tests. In each temperature environment, the battery was charged and discharged 100 times at a rate of 0.1C to evaluate the battery's cycle performance and high temperature stability at different temperatures.

[0096] Test steps: The battery was charged and discharged 100 times at 45°C, 55°C and 65°C respectively, and the capacity change, internal resistance increase and voltage range of the battery before and after the test were tested. After the high temperature cycle test, the electrochemical impedance spectroscopy (EIS) method was used to detect the internal resistance of the battery and analyze the effect of high temperature on battery performance.

[0097] Data Collection: After each cycle, the discharge capacity was recorded, and the capacity retention rate, internal resistance increase, and voltage range of the battery during charge and discharge were tested at different temperatures. Finally, the performance differences of the two groups of batteries at different temperatures were compared.

[0098] Experimental data: Table 5: High temperature stability test data Summary: The battery of Example 5 performs significantly better than that of Comparative Example 5 under high temperature conditions. Even after 100 cycles at 65°C, the battery of Example 5 still maintains a relatively high discharge capacity, and the internal resistance increases relatively slowly. This phenomenon can be attributed to the pre-lithiation treatment of the hard carbon particles and the core-shell structure of the positive electrode design. The pre-lithiation hard carbon negative electrode provides more stable cycle performance at high temperatures, reduces excessive expansion and structural failure of the electrode material, and especially effectively improves the thermal stability at high temperatures.

[0099] In contrast, the battery of Comparative Example 5 significantly decayed under high temperature. As the temperature rises, the discharge capacity of the battery gradually decreases and the internal resistance increases rapidly, which indicates that the conventional hard carbon negative electrode and the sodium cobalt oxide positive electrode are more likely to undergo structural changes under high temperature conditions, resulting in capacity decay and increased internal resistance. This difference reflects the significant advantages of the battery material of the present invention in high temperature stability, and has a stronger ability to resist thermal failure.

[0100] The present invention optimizes the design of electrode materials, especially exhibiting excellent cycle stability under high temperature conditions. This shows that the battery of Example 5 not only has excellent performance under normal temperature conditions, but can also effectively maintain a good capacity retention rate and low internal resistance under high temperature environments, greatly broadening its applicability in high temperature applications. For example, in fields such as electric vehicles and energy storage systems that require high temperature adaptability, the battery of the present invention has stronger market potential.

[0101] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A low negative pressure sodium battery, characterized in that: It includes negative electrode materials, positive electrode materials, electrolyte and separator, among which: The negative electrode material is pre-lithiation treated hard carbon particles with a particle size of 5-10 μm and a polyvinylidene fluoride-hexafluoropropylene functional layer coated on the surface; The cathode material is a core-shell structure, including: The core layer is made of layered oxide material NaNi x Mn 1-x O2 composition, where x is 0.7-0.8; The shell is composed of sodium phosphate, and the mass of the shell accounts for 5-15% of the total mass of the positive electrode; The electrolyte includes sodium hexafluorophosphate, ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, a sodium salt concentration of 0.8-1.2M, and additives include fluoroethylene carbonate in an addition ratio of 2-5% and N-methyl-N-propylpyrrolidinium bisfluorosulfonimide in an addition ratio of 15-25%; The diaphragm is a porous diaphragm with a porosity of 40-50% and a thickness of 16-25 μm.

2. A low negative pressure sodium battery according to claim 1, characterized in that: The porosity of the hard carbon particles of the negative electrode material is 25-40%.

3. A low negative pressure sodium battery according to claim 1, characterized in that: The core layer grain size of the positive electrode material is 1-5 μm.

4. A method for preparing a low negative pressure sodium battery, characterized in that: The following steps are involved: S1. Preparation of negative electrode material: Mix hard carbon particles and lithium metal sheets in a mass ratio of 1:0.4-0.6, heat treat at 400-450°C for 2-3h, and after cooling, coat the surface with 3-6% polyvinylidene fluoride-hexafluoropropylene solution, and heat treat at 70-100°C after drying; S2. Preparation of positive electrode materials: Sodium carbonate, nickel oxide and manganese oxide are weighed in a molar ratio of 1:0.7-0.8:0.2-0.3, ball-milled for 10-12 hours, pre-sintered at 500-550°C for 5-7 hours, and then sintered at 850-900°C for 10-12 hours to form a core layer; The core material is coated with a sodium phosphate solution, dried, and then sintered at 500-550°C for 3-5h to form a shell layer; S3, electrolyte preparation: 0.8-1.2M sodium hexafluorophosphate is dissolved in a mixed solvent of EC:DMC with a volume ratio of 1:1, 2-5% fluoroethylene carbonate and 15-25% N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide are added, and stirred evenly; S4. Battery assembly: stack the positive electrode, separator and negative electrode in sequence, inject the electrolyte and seal, and perform 3-5 pre-cycles at a rate of 0.05C.

5. A method for preparing a low negative pressure sodium battery according to claim 4, characterized in that: The heat treatment atmosphere in the preparation of the negative electrode material in step S1 is high-purity argon gas, and the argon gas flow rate is 50-100 ml / min.

6. A method for preparing a low negative pressure sodium battery according to claim 4, characterized in that: In the step S2, the positive electrode material is prepared by an immersion coating method.

7. The method for preparing a low negative pressure sodium battery according to claim 4, characterized in that: In the step S3, the stirring speed in the preparation of the electrolyte is 300-600 rpm, the stirring time is 2-4 hours, and the water content in the solution is controlled below 10 ppm.

Citation Information

Patent Citations

  • Method for solving flatulence of lithium titanate cathode of lithium battery by using double-boundary wrapping

    CN103187562A

  • High-first-effect hard carbon negative electrode material, preparation method thereof and sodium ion battery

    CN114914428A

  • Hard carbon negative electrode material and preparation method thereof, mixed negative electrode material and secondary battery

    CN115893369A

  • Composite ultrathin lithium foil and preparation method and application thereof

    CN117525268A

  • Core-shell type sodium ion battery positive electrode material and preparation method thereof

    CN117712356A